2010
DOI: 10.1089/thy.2009.0264
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Thyroid Cysts May Be a Cause of Hypothyroidism in Patients with Relatively High Iodine Intake

Abstract: Although these patients were from a region with high-iodine intake and had a relatively high intake compared with most regions of the world, this amount of iodine intake is not associated with hypothyroidism in otherwise healthy persons. Therefore, we propose that multiple thyroid cysts, which we have termed polycystic goiter, is probably a cause of hypothyroidism in patients with a relatively high iodine intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
0
15
1
1
Order By: Relevance
“…These pathological features were identified in all the presented cases with PCTD, and may be the cause of PCTD. We previously reported that the tissue between the cysts detected by ultrasound was hypo-echoic and had a sponge-like appearance in the PCTD patients [1]. The huge follicles seemed to be cysts and the area with moderately large follicles appeared as hypoechoic lesions on ultrasound.…”
Section: Comparison Of Normal-looking Thyroid Tissuementioning
confidence: 88%
See 1 more Smart Citation
“…These pathological features were identified in all the presented cases with PCTD, and may be the cause of PCTD. We previously reported that the tissue between the cysts detected by ultrasound was hypo-echoic and had a sponge-like appearance in the PCTD patients [1]. The huge follicles seemed to be cysts and the area with moderately large follicles appeared as hypoechoic lesions on ultrasound.…”
Section: Comparison Of Normal-looking Thyroid Tissuementioning
confidence: 88%
“…
Polycystic thyroid disease (PCTD) is characterized by multiple thyroid cysts detected by ultrasonography, the absence of thyroid autoantibodies, and susceptibility to the development of hypothyroidism due to a high iodine intake [1]. We previously reported that hypothyroidism induced by PCTD accounted for about 7% of all causes of hypothyroidism in a region with a high iodine intake [2].
…”
mentioning
confidence: 99%
“…On the other hand, regardless of chronic thyroiditis, group C, which showed a higher titer of TSH before treatment than group D, showed a higher dose of LT4 before delivery than group D. Because this study was retrospective, the causes of SCH besides chronic thyroiditis could not be clarified adequately. However, we suspected that these subjects were probably suffering from mild chronic thyroiditis showing a negative titer of anti-thyroid antibody or polycystic thyroid disease, which is one of the causes of hypothyroidism associated with multiple thyroid cysts influenced by high iodine intake [16]. In addition, high iodine intake might influence their thyroid function because Japan is an area of high iodine intake.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-needle aspiration biopsy is not necessary for such small cysts, even though such children present positive or negative for thyroid autoantibodies. Recently, it has been reported that multiple small cysts in the whole thyroid gland may be a cause of hypothyroidism in old patients with relatively high iodine intake [14]. Such patients presented negative for thyroid autoantibodies, and the disease was named polycystic thyroid disease [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that multiple small cysts in the whole thyroid gland may be a cause of hypothyroidism in old patients with relatively high iodine intake [14]. Such patients presented negative for thyroid autoantibodies, and the disease was named polycystic thyroid disease [14]. These multiple small cysts are diffusely located in the whole thyroid glands, not aggregated in some area.…”
Section: Discussionmentioning
confidence: 99%